A Review Paper on Fused Deposition Modeling a Part and Process Parameters - Kumar, Vinod (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
The Fused Deposition Modeling is one of the most popular a Manufacturing and technologies for various application in Engineering field. Fdm Process has introduced commercially early strata yes in USA. The Focus of industries have Shifted from traditional Product development in metrology to rapid fabrication technology. The fused deposition modeling is one of the easy manufacturing to directly in cad design by laser Prototyping technology create data. The Process parameter is(FDM)improving to the quality of Part. The fused deposition modeling used to complicated model of machine are easy design in technology.